Conservation and Restoration of Maya Architectural Heritage - Muñoz Cosme, Gaspar (Restauro Compás y Canto S.A., 2021)
The debate about the conservation of Maya architecture began from the first investigations and excavations in the Maya area. Having been buried for hundreds of years, this architecture was at serious risk after its excavation. The remarkable monumental buildings built by the ancient Maya over a thousand years ago are a cultural heritage that must be researched and preserved for its archaeological, architectural, cultural and social values. The uniqueness of Maya monumental architecture, recognized as a world heritage, together with its historical process of abandonment and subsequent recovery through archaeological research, lead us to think about the methods and criteria that should be used to ensure that, once excavated, this architecture can be preserved with all its values for current and future societies as one of the most notorious legacies of this ancient civilization. The experience of more than thirty years of excavations and restorations in the Maya area allows to obtain a critical view of the methods and results. Through the analysis of some specific cases, and taking into account the new instruments of research, documentation and analysis of Maya architecture, it is discussed which should be the most appropriate criteria of conservation.